Pakistan between Parliamentarianism and Federalism: A Judicial Activism Perspective - Muhib Ullah Khan; Tariq Ullah; Karam Elahi; Usman Khan (Indus Journal of Social Sciences, 2025)
The compatibility of state structure and model of governance have contributed to the consolidation of democracies in various societies. However, the case of Pakistan is different where the state organization and form of governance incompatibility have weakened the growth of democracy. This research article answers the question: How does parliamentary system of governance work under the federal state structure in Pakistan? The question has been discussed in light of AV Dicey’s parliamentary governance under the unitary state. Interpretive approach under qualitative research method has been adopted for the data collected. Interviews have been conducted with various persons belonging to different fields. The manuscript argues that model of governance and state organization unlike the developed and some of the under-developed countries have been one of the obstacles in the way of successful parliamentary democracy in Pakistan. It further argues that the higher judiciary, the cornerstone of federalism, complicates parliamentarianism in Pakistan.